Investigating the rheological properties of crumb rubber modified bitumen and its correlation with temperature susceptibility - Nuha Salim Mashaan; Mohamed Rehan Karim (Materials Research, 2013)
There is substantial evidence on the advantages of using crumb rubber in enhancing conventional bitumen properties, gaining environmental protection and boosting industrial-economical benefits. Thus, the use of this ingenious additive in bitumen modification through sustainable technology is highly advocated.The main objective of this research is to investigate the effects of different blending conditions (of time and temperature) and various crumb rubber contents on the properties of bitumen binders. Testing was conducted using the Dynamic shear rheometer (DSR) test and softening point test. The results showed that differing crumb rubber contents and blending temperature have significant effects on modified binder properties whereas the blending time showed an insignificant effect. Higher blending temperature and crumb rubber content were found to influence the interaction of bitumen-rubber blends and also increased the swelling rate of rubber particles, resulting in an increase in complex shear modulus (G*), storage modulus (G'), loss modulus (G") and softening point as well as a decrease in phase angle (δ). Thus, the modified bitumen became less susceptible to deformation after stress removals. The study also presented a considerable relationship between rheological parameters (G*, G', G' and δ) and softening point in terms of predicting physical-mechanical properties regardless of blending conditions. Thus, in terms of elasticity for the softening point data, the storage modulus and phase angle were found to be good indicators of binder elasticity. When softening point is made available, a prediction about binder ability to recover its original shape after stress removals can be done.